Establishment of Vandua and Cryptocasia, two neglected lineages of the tribe Colocasieae (Araceae) - Ma, Zhengxu; Mayo, Simon J.; Liang, Ke (Jungle) (Phytotaxa, 2026)
The Alocasia–Colocasia group (Araceae) has an intricate taxonomic history, with traditional generic circumscriptions of the two major genera, Alocasia and Colocasia, being challenged by phylogenetic evidence. Current phylogenetic and morphological evidence together confirm that the two lineages—Alocasia evrardii-A. vietnamensis and Colocasia affinis-C. fallax—are distinct and coherent groups whose current generic placements in the tribe Colocasieae stand in contrast to the established classification. We here formally describe two new genera to accommodate this situation: Vandua and Cryptocasia. Vandua is characterised by its tuberous, epiphytic or lithophytic habit; production of bulbiliferous stolons; a pistillate zone flanked by two clusters of pistillodes, with the basal cluster specialised into a basal sterile zone; absence of interspersed staminodes; ovaries with 4–5 ovules in parietal placentation; and single-seeded berries. Cryptocasia differs from Colocasia sensu stricto by its small plant size, the presence of a basal sterile zone, and a pistillate zone lacking interspersed staminodes. Recognition of these genera resolves long-standing inconsistencies between phylogenetic and morphological evidence, providing a preliminary circumscription of Alocasia and Colocasia and a firmer basis for establishing a natural systematic framework for the tribe.